Buy coal, cap gas! Markets for fossil fuel deposits when fuel emission intensities differ - Angelika Vogt; Achim Hagen; Klaus Eisenack (Humboldt-Universität zu Berlin, Faculty of Life Sciences, Department of Agricultural Economics, 2020)
Climate policies can target either the demand or the supply of fossil fuels. While demandside policies have been analyzed in the literature and applied in policy-making, supply-side policies, e.g. deposit policies, are a promising option and a recent research focus. In this paper we study deposit markets for two fuels that differ in emission intensity. We find that, with strategic action on the deposit markets, deposit policies are inefficient due to price manipulations within and between both deposit markets. Regarding the political economy of deposit policies, they generate more welfare for all countries if applied to both fuels as opposed to one or none. Further, for perfectly segmented fuel markets, importing countries do not purchase deposits of a sufficiently clean fuel. If fuels are substitutes and strongly differ in emission intensity, countries do not buy deposits of a relatively clean fuel. Finally, deposit markets can induce countries selling deposits to choose a cleaner fuel mix.
Keywords: Q31; Q38; 330; Fossil fuel; Climate policy; Deposit market; Carbon leakage